FINANCIAL LITERACY AND STUDENTS' FINANCIAL BEHAVIOR: MODELING THE MEDIATING IMPACT OF PAYLATER PERCEPTIONS - Sumardi, Umar; Harlina, Harlina (Distribusi - Journal of Management and Business, 2025)
The purpose of this study is to determine how students' financial literacy influences their financial behavior through their impact and perceptions in using paylater. This research is a quantitative research using data obtained through the distribution of questionnaires to be further analyzed using the Structural Equation Modeling (SEM) – Partial Least Square (PLS) statistical test. The analysis results show that financial literacy has a positive but insignificant effect on financial behavior. Meanwhile, financial literacy has a positive and significant effect on impact and perception. Furthermore, impact and perception are also found to have a positive and significant effect on financial behavior. Finally, the effect of financial literacy on financial behavior is demonstrated through the impact and perception of financial use.paylater has a positive but not significant relationship. This study provides a new perspective by introducing the impact and perception of paylater use as a mediating variable. Furthermore, the hypothesis testing results successfully identified the complexity of the relationship between financial literacy and financial behavior, with the analysis concluding a positive but insignificant effect. The implications of this study imply that financial literacy is a fundamental factor that shapes how individuals act towards financial decisions. The results showing that the impact and perception of paylater use have a positive and significant influence on financial behavior indicate that impact and perception can act as mediating variables, indicating that to change financial behavior, it is important to first focus on how individuals process information and form their views about finances.